1976
DOI: 10.1093/cvr/10.2.254
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical changes associated with development and reversal of cardiac hypertrophy in spontaneously hypertensive rats

Abstract: This study is the first report describing the sequence of biochemical alterations of myocardium during the progression of naturally occurring hypertrophy in spontaneously hypertensive rats (SHRs) and then with its reversal by alpha-methyldopa therapy. Changes in DNA, RNA, hydroxyproline, as well as incorporation of 14C lysine into cardiac myosin, were compared with the pattern found in suitably matched controls. A significant increase in RNA, hydroxyproline, and 14C incorporation was observed in SHRs. Antihype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
28
1

Year Published

1977
1977
1989
1989

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(34 citation statements)
references
References 0 publications
5
28
1
Order By: Relevance
“…31 Some of the attributes of the SHR that confound studies of hypertension-induced hypertrophy include 1) the increased ventricular mass present from the first week of life, 32 which becomes very pronounced by 33 days of age 33 ; 2) arterial blood pressures significantly higher in SHR as compared with control Wistar-Kyoto rats as early as 14 days of age 34 ; and 3) progressive left ventricular hypertrophy in young, prehypertensive SHR. 35 " 37 Basically, the issue is that, apparently because of a strong genetic drive, SHR are probably born with cardiac hypertrophy and circulatory defects that make baseline data difficult to obtain and the identification of proper control animals difficult.…”
Section: Discussionmentioning
confidence: 99%
“…31 Some of the attributes of the SHR that confound studies of hypertension-induced hypertrophy include 1) the increased ventricular mass present from the first week of life, 32 which becomes very pronounced by 33 days of age 33 ; 2) arterial blood pressures significantly higher in SHR as compared with control Wistar-Kyoto rats as early as 14 days of age 34 ; and 3) progressive left ventricular hypertrophy in young, prehypertensive SHR. 35 " 37 Basically, the issue is that, apparently because of a strong genetic drive, SHR are probably born with cardiac hypertrophy and circulatory defects that make baseline data difficult to obtain and the identification of proper control animals difficult.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast. Sen et al 16 indicated a significant decrease of DNA concentration in the SHR although an increased total content was shown in the young SHR. An explanation for the discrepancy is the difference in the normotensive control rats used in each experiment.…”
Section: :1mentioning
confidence: 95%
“…15 An increase of RNA content was also observed in the SHR heart. 16 " However, there are two conflicting reports concerning the amount of myocardial DNA content in the SHR. 16 l7 In previous experiments described in Part 1 (pp 864-872), it was shown that the heart weight of rats is a highly heritable trait, and that the effect of genetic factors upon cardiac enlargement is larger than that of elevated blood pressure at a young age.…”
mentioning
confidence: 99%
“…3 ' 4 We, 2 ' *~7 as well as others, 8 "" have shown that factors other than blood pressure controls are involved in the development or reversal of myocardial hypertrophy in hypertension. Several hypotheses can be advanced to account for the factors) responsible for an increase in muscle mass as a result of increased protein synthesis.…”
mentioning
confidence: 94%